The Level Of Education Is Able To Determine The Behavior Of The Use Masks As A Prevention Of Coronavirus Disease 2019 in the City of Batam Kepulauan Riau - Victor E. D Palapessy; Muhammad Rakib Latuconsina; Sahrir Sillehu (International Journal of Science, Technology & Management, 2021)
Cases of covid-19 in Indonesia, first appeared on June 02 March 2020 as much as 2 cases. In May 2020, the number of deaths is still rising despite also cure the patient. Until September 11, 2020, the case of positive covid-19 increased by as much as 3.737. So a total of 210.940 people. While for the case of recovery, there are the addition of as much as 2.707 the person bringing the total to 150.217 people. Then for patients who died increased to 88 people so that the total of patients who died 8.544 people (Compass, 2020). One way the most easy to do to prevent the virus's spread in the community is to use a mask, but still often seen there are some people who go without using a mask. The purpose of this study is to determine the influence of age, gender, education, employment status, type of mask of the behavior of the use of masks as a prevention of coronavirus disease 2019 in the City of Batam. This Research is a quantitative research, using the approach of the study cross sectional. The sample in this study as many as 100 respondents. The instrument used was a questionnaire. Data analysis in this study using SEM PLS. The results of the research showed that gender, type of mask, education, employment status and age have a positive and significant impact on the behavior of use of the mask. The variables that most influence the variable behavior of the use of the mask that the education variable (0,316), employment status (0,275), age (0,216), gender (0,212), and the type of mask (to 0.149). Education last owned by a person can affect the behavior of existing in itself, in this case associated with the use of the mask.